KAJIAN YURIDIS KEDUDUKAN MAHKAMAH KONSTITUSI SEBAGAI POSITIF LEGISLATOR MELALUI MEKANISME JUDICIAL REVIEW - NIM. A1011181056, YUSTINA VENERANDA NOVI (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstractThe Constitutional Court is one of the implementations of judicial power in Indonesia. The authority attached to the Constitutional Court can be seen in Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia (UUD NRI Tahun 1945). Testing the Law or what is commonly called Judicial Review is one of them, as part of the check and balance process. In terms of testing the law, the Constitutional Court uses the 1945 Constitution as its